Cecelia and Fanny : the remarkable friendship between an escaped slave and her former mistress - Asher, Brad, 1963- (The University Press of Kentucky, 2011)
Cecelia was a fifteen-year-old slave when she accompanied her mistress, Frances "Fanny" Thruston Ballard, on a holiday trip to Niagara Falls. During their stay, Cecelia crossed the Niagara River and joined the free black population of Canada. Although documented relationships between freed or escaped slaves and their former owners are rare, the discovery of a cache of letters from the former slave owner to her escaped slave confirms this extraordinary link between two urban families over several decades. Cecelia and Fanny: The Remarkable Friendship between an Escaped Slave and Her Former Mistress is a fascinating look at race relations in mid-nineteenth-century Louisville, Kentucky, focusing on the experiences of these two families during the seismic social upheaval wrought by the emancipation of four million African Americans. Far more than the story of two families, Cecelia and Fanny delves into the history of Civil War-era Louisville. Author Brad Asher details the cultural roles assigned to the two women and provides a unique view of slavery in an urban context, as opposed to the rural plantations more often examined by historians